2017
DOI: 10.1007/s10877-017-0055-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled anesthetic agent sedation in the ICU and trace gas concentrations: a review

Abstract: There is a growing interest in the use of volatile anesthetics for inhalational sedation of adult critically ill patients in the ICU. Its safety and efficacy has been demonstrated in various studies and technical equipment such as the anaesthetic conserving device (AnaConDa™; Sedana Medical, Uppsala, Sweden) or the MIRUS™ system (Pall Medical, Dreieich, Germany) have significantly simplified the application of volatile anesthetics in the ICU. However, the personnel's exposure to waste anesthetic gas during dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 83 publications
0
15
0
2
Order By: Relevance
“…VA pollution below 2 ppm is considered minimal in most cases. Although the mean time‐weighted exposure limits for ISO, SEVO, and DES vary between countries, most studies have found that concentrations of 2‐50 ppm for ISO, 5‐20 ppm for SEVO, and 5‐20 ppm for DES per 8‐hour working days are likely safe for healthcare professionals (Table ) . In this study, most peak concentrations were within these limits and only a few exceeded the global lowest threshold limit concentration of 2 ppm for ISO, as recommended by Norwegian guidelines and the National Institute for Occupational Safety and Health …”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…VA pollution below 2 ppm is considered minimal in most cases. Although the mean time‐weighted exposure limits for ISO, SEVO, and DES vary between countries, most studies have found that concentrations of 2‐50 ppm for ISO, 5‐20 ppm for SEVO, and 5‐20 ppm for DES per 8‐hour working days are likely safe for healthcare professionals (Table ) . In this study, most peak concentrations were within these limits and only a few exceeded the global lowest threshold limit concentration of 2 ppm for ISO, as recommended by Norwegian guidelines and the National Institute for Occupational Safety and Health …”
Section: Discussionmentioning
confidence: 50%
“…Although several studies proved patient safety of VA application, occupational exposure to anaesthetic agents has been a cause for concern among ICU staff . Inconsistent threshold limit concentrations for ISO, SEVO, and DES between countries and poor air‐conditioning in ICUs compared to operating rooms amplify the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, measurements of the baseline values demonstrated that trace concentrations of interfering agents are always detectable, even in an experimental setting. Lastly, the ACD is not registered for DES, because it can boil in the agent line due to its low boiling point, which may result in an unintended emission of gas boluses [3]. However, we did not observe an uneven discharge of the anesthetic.…”
Section: Discussionmentioning
confidence: 80%
“…Occupational anesthetic gas exposure is attracting growing interest, since studies have shown that low-dose exposure to volatile anesthetics (VA) increases the number of DNA strand breaks and the micronuclei frequencies in lymphocytes and epithelial cells [1, 2]. Although exposure levels of healthcare professionals have been minimized, it still is good clinical practice to reduce gas pollution ‘as low as reasonably achievable’ [3]. The Occupational Safety and Health Administration of the United States recommends the control of VA exposure by engineering controls, good work practices, use of personal protective equipment, administrative controls, and personnel exposure and environmental monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Their effects after long(er) term use in the ICU remain less well studied, but the review by Manatpon and Kofke [13] reads reassuring. Finally, ICU contamination by trace gases and its clinical significance is reviewed [14].…”
mentioning
confidence: 99%